2016
DOI: 10.1177/1362168816654169
|View full text |Cite
|
Sign up to set email alerts
|

Task repetition effects on L1 use in EFL child task-based interaction

Abstract: Research has shown that tasks provide second language (L2) learners with many opportunities to learn the L2. Task repetition has been claimed to benefit L2 learning since familiarity with procedure and/or content gives learners the chance to focus on more specific aspects of language. Most research on task repetition has focused on adult populations, but child learners are an under-researched group. The same goes for first language (L1) use during L2 interaction, which has been mainly studied among adult L2 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 44 publications
6
43
0
Order By: Relevance
“…García Mayo et al (2018) investigated the effects of task repetition with children (aged 7-9) using a spot the differences task (cowboy task) and found that it positively affected children's accuracy as well as their fluency. Azkarai and García Mayo (2016) working with 9-10 year old children using a spot the differences task found that the children did not use the L1 extensively and their overall L1 use also declined by the second encounter with the task. Although the results from these studies remain tentative and the authors suggest that much more research should be undertaken with different age groups and different types of tasks in different contexts, overall there is a strong consensus that task repetition has a positive effect.…”
Section: Task Repetition and Its Benefitsmentioning
confidence: 99%
“…García Mayo et al (2018) investigated the effects of task repetition with children (aged 7-9) using a spot the differences task (cowboy task) and found that it positively affected children's accuracy as well as their fluency. Azkarai and García Mayo (2016) working with 9-10 year old children using a spot the differences task found that the children did not use the L1 extensively and their overall L1 use also declined by the second encounter with the task. Although the results from these studies remain tentative and the authors suggest that much more research should be undertaken with different age groups and different types of tasks in different contexts, overall there is a strong consensus that task repetition has a positive effect.…”
Section: Task Repetition and Its Benefitsmentioning
confidence: 99%
“…Yet it has been shown that just as differences exist between adults and children, so do differences between younger and older child learners. Age differences for children have been found in interaction studies (e.g., in ESL settings: Oliver, 1998, 2002, 2009; in EFL settings: Azkarai & García Mayo, 2016; Azkarai & Imaz Agirre, 2016; Butler & Zeng, 2014, 2015; García Mayo & Lázaro Ibarrola, 2015), particularly in relation to task use (e.g., in ESL settings: Oliver, 1995, 1998, 2002; in EFL settings: Azkarai & Imaz Agirre, 2016) and task repetition (e.g., in ESL settings: Mackey et al, 2007; in EFL settings: Azkarai & García Mayo, 2016; García Mayo & Imaz Agirre, 2016).…”
Section: Age and Child Slamentioning
confidence: 97%
“…In a more comprehensive study, Azkarai and García Mayo (2016) explored the use and functions the L1 served in child EFL task repetition. Forty-two Spanish EFL learners (9–10 years old) participated in their study, which involved a spot-the-differences task.…”
Section: Sociocultural Perspective and Child Sla Researchmentioning
confidence: 99%
“…One-way tasks, by contrast, foster a unidirectional type of flow because the learner in need of the information would have to negotiate for information more than their partner (Gass & Varonis, 1985). Consequently, tasks have become a fixture in recent interaction-based studies (Azkarai & García Mayo, 2017;García Mayo & Lázaro-Ibarrola, 2015;Hidalgo, 2019;Pinter, 2006Pinter, , 2007. However, a study by Galaczi (2014) on the interactional competence of learners revealed that, the lower the level of command of the TL, the higher the difficulty in maintaining a balanced interaction between participants.…”
Section: Tasks In Interaction-based Studiesmentioning
confidence: 99%